Are there gender-related influences on corporate sustainability? A study of women on boards of directors - Galbreath, Jeremy (eContent Management Pty Ltd, 2011)
This study sought to investigate if there is a link between women on boards of directors and corporate sustainability, which included three dimensions: 1) economic; 2) environmental; and 3) social. Using a sample of publicly-listed firms from Australia, the results suggest some level of support that a link exists between women directors and corporate sustainability. Gender diversity is expected to impact on ‘good’ governance, thereby minimizing affects of subversion or misappropriation of shareholder funds that can be detrimental to their returns. Accordingly, findings confirm a positive link between women on boards and economic growth. Because of their relational abilities, women on boards are more likely able to engage with multiple stakeholders and respond to their needs, resulting in an avenue for demonstrating social responsiveness, which is confirmed by the results. However, due to their backgrounds and work experiences, sex-based biases and stereotyping might exist in boardrooms with men directors discounting input from women directors on issues relating to environmental integrity. The results of this study find that women directors are not significantly associated with environmental integrity. Discussion is given to these findings along with paths for future research.